Conceitos do controle de qualidade de equipamentos de raios-X para a proteção radiológica em serviços de saúde - Fernandes, Marco Antonio Rodrigues [UNESP]; Kanezawa, Jorge Shozuke (My University, 2010)
The work presents basic concepts of radiologic protection seeking to guide the professionals that use equipments issuing of ionization radiation as for his correct handling. They were appraised 1665 X-ray equipments installed in dentist clinics and radiology services, among 1996 to 2003, in the Araçatuba region. Radiometry tests quantify the radiological parameters according to the legislation. Equipments of the type dental periapical corresponded to 66% of the total, 32% are apparels of medical radiology and 8% are apparels dental panoramic. The lenght of the localizator cone was the parameter with larger number of disconformities, this contributes to inadequacies of the radiation dose rate and of the field size in the patient's skin. The study alert for the need of specific trainings to the professionals of the area.

O trabalho apresenta conceitos básicos de proteção radiológica visando orientar os profissionais que utilizam equipamentos emissores de radiação ionizante quanto ao seu correto manuseio. Foram avaliados 1665 equipamentos de raios-X instalados em clínicas odontológicas e serviços de radiologia, entre 1996 a 2003, na região de Araçatuba. Testes de radiometria quantificam os parâmetros radiológicos conforme a legislação. Equipamentos do tipo odontológico periapical corresponderam a 66%, 32% são aparelhos de radiologia médica e 8% são aparelhos odontológicos panorâmicos. O comprimento do localizador foi o parâmetro com maior número de desconformidades, isto contribui para inadequações da taxa de dose de radiação e do tamanho de campo na pele do paciente. O estudo alerta para a necessidade de treinamentos específicos aos profissionais da área.
Concepts of the quality control of X-rays equipments for the radiologic protection in health services
Keywords: Araçatuba; Radiology; Radiometry; X-ray; Araçatuba; Radiologia; Radiometria; Raios-X